Genetically superior European sea bass (Dicentrarchus labrax) and nutritional innovations: Effects of functional feeds on fish immune response, disease resistance, and gut microbiota - Simona Rimoldi; Daniel Montero; Silvia Torrecillas; Antonio Serradell; Felix Acosta; Pierrick Haffray; Barbara Hostins; Ramon Fontanillas; François Allal; Aline Bajek; Genciana Terova (Aquaculture Reports, 2023)
The objective of this study was to determine if selected fish genotypes could benefit from the use of functional additives in novel aqua feed formulations to improve growth performance, gut microbiota, immune response, and disease resistance in fish. Two batches of juvenile European sea bass selected for high growth (HG; selected sires x selected dams), and wild types (WT; wild sires x selected females) were fed a “future diet” coated with three different functional additives for 12 weeks as follows: (i) 2 weeks with a high dose, followed by (ii) 10 weeks with a low dose. The functional additives tested were a mixture of probiotics (PROB), organic acids (ORG), and phytogens (PHYTO). A pathogen challenge test (Vibrio anguillarum) and a stress condition (overcrowding) were performed after each dose. At the end of the feeding experiment, fish from the HG group performed better than fish from the WT group in terms of body weight, relative growth, SGR, and DGI. The results of the two challenge tests performed after two weeks of high dose and ten weeks of low dose showed a significant effect of diet on fish survival. GALT-associated gene expression analysis revealed an interaction between the genotype and diet for il-1β in the distal gut. Finally, regarding the gut microbiota, discriminant analysis showed no clear separation between fish fed the future diet and those fed the same diet with experimental additives. Nevertheless, the relative abundance of certain taxa varied between experimental groups. For example, fish fed the ORG diet had higher relative abundance of Streptococcus in both genotypes, whereas fish fed the PHYTO diet had higher abundance of Lactobacillales. In contrast, fish fed PROB had lower abundance of Pseudomonas and Acinetobacter.